Mannan-MOG35-55 Reverses Experimental Autoimmune Encephalomyelitis, Inducing a Peripheral Type 2 Myeloid Response, Reducing CNS Inflammation, and Preserving Axons in Spinal Cord Lesions - Dagkonaki, Anastasia; Avloniti, Maria; Evangelidou, Maria; Papazian, Irini; Kanistras, Ioannis; Tseveleki, Vivian; Lampros, Fotis; Tselios, Theodore; Jensen, Lise Torp; Möbius, Wiebke; Ruhwedel, Torben; Androutsou, Maria-Eleni; et al. (Frontiers in Immunology, 2020)
CNS autoantigens conjugated to oxidized mannan (OM) induce antigen-specific T cell tolerance and protect mice against autoimmune encephalomyelitis (EAE). To investigate whether OM-peptides treat EAE initiated by human MHC class II molecules, we administered OM-conjugated murine myelin oligodendrocyte glycoprotein peptide 35-55 (OM-MOG) to humanized HLA-DR2b transgenic mice (DR2b.Ab°), which are susceptible to MOG-EAE. OM-MOG protected DR2b.Ab° mice against MOG-EAE by both prophylactic and therapeutic applications. OM-MOG reversed clinical symptoms, reduced spinal cord inflammation, demyelination, and neuronal damage in DR2b.Ab° mice, while preserving axons within lesions and inducing the expression of genes associated with myelin (Mbp) and neuron (Snap25) recovery in B6 mice. OM-MOG-induced tolerance was peptide-specific, not affecting PLP178-191-induced EAE or polyclonal T cell proliferation responses. OM-MOG-induced immune tolerance involved rapid induction of PD-L1- and IL-10-producing myeloid cells, increased expression of Chi3l3 (Ym1) in secondary lymphoid organs and characteristics of anergy in MOG-specific CD4+ T cells. The results show that OM-MOG treats MOG-EAE in a peptide-specific manner, across mouse/human MHC class II barriers, through induction of a peripheral type 2 myeloid cell response and T cell anergy, and suggest that OM-peptides might be useful for suppressing antigen-specific CD4+ T cell responses in the context of human autoimmune CNS demyelination.